Pengaruh Penggunaan Telur yang Diawetkan Dengan Parafin dan Penggunaan Sodium Bikarbonat Terhadap Sifat-Sifat Fisikawi, Kimiawi dan Organoleptik Kerupuk Telur - Zulfatunnisa Zulfatunnisa; Agus Susilo; Imam Thohari (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2015)
The materials used in this research were egg crackers made from albumen, tapioca, wheat flour, garlic, salt, water and sodium bicarbonate. The variables measured were expansion power, breaking force, water content, protein content, mineral content and organoleptic quality (colour, flavour, crispiness). Data were analized with analysis of variance and followed by Duncan's Multiple Range Test.The result showed that the preservation with paraffin and the use of sodium bicarbonate had a highly significant effect (P<0.01) on expansion power, breaking force, water content, protein content, minerals content and organoleptic quality (colour, flavour and crispiness). It's interaction had a highly significant effect (P<0.01) on protein content and organoleptic quality (flavour and crispiness) of eggcrackers. It is found that egg coated with paraffin can be kept for 60 days had highfoaming foroe similar value with egg without preservation however, it haddisadvantages on expansion poweq breaking force and colour than fresh egg, so suggested to improve by use increase quantity albumen and decrease the Use of Sodium bicarbonate.